Informant‐based tools for assessment and monitoring of cognition, behavior, and function in neurocognitive disorders: Systematic review and report from a CCCDTD5 Working Group. (19th January 2022) - Choudhury, Samira; Ghodasara, Sheena; Stiffel, Michael; Fischer, Corinne E.; Tang‐Wai, David F.; Smith, Eric Edward; Massoud, Fadi; Robin Hsiung, Ging‐Yuek; Lee, Linda; Bruneau, Marie‐Andrée; Laforce, Robert Jr; Ismail, Zahinoor; et al.
Abstract: Objective: As part of the fifth Canadian Consensus Conference on the Diagnosis and Treatment of Dementia, we assessed the literature on informant‐based tools for assessment and monitoring of cognition, behavior, and function in neurocognitive disorders (NCDs) to provide evidence‐based recommendations for clinicians and researchers. Methods: A systematic review was conducted following Preferred Reporting Items for Systematic Reviews and Meta‐Analyses standards guidelines. Publications that validated the informant‐based tools or described their key properties were reviewed. Quality of the studies was assessed using the modified Quality Assessment tool for Diagnostic Accuracy Studies. Results: Out of 386 publications identified through systematic search, 34 that described 19 informant‐based tools were included in the final review. Most of these tools are backed by good‐quality studies and are appropriate to use in clinical care or research. The tools vary in their psychometric properties, domains covered, comprehensiveness, completion time, and ability to detect longitudinal change. Based on these properties, we identify different tools that may be appropriate for primary care, specialized memory clinic, or research settings. We also identify barriers to use of these tools in routine clinical practice. Conclusion: There are several good‐quality tools available to collect informant‐report for assessment and monitoring of cognition, behavior, or function in patients with NCDs. Clinicians and researchers may choose a particular tool based on their specific needs such as domains of interest, desired psychometric properties, and feasibility. Further work is needed to make the tools more user‐friendly and to adopt them into routine clinical care. Key points: A subgroup of the fifth Canadian Consensus Conference on the Diagnosis and Treatment of Dementia assessed the current literature regarding informant‐based tools for assessment and monitoring of neurocognitive disorders (NCDs). We identified 19 informant‐based tools that can complement the assessment of cognition, function, and behavior in NCDs. We described the key properties of these tools including their strengths and weaknesses that are relevant for their adoption in routine clinical or research use. We discuss barriers to use of these tools in routine clinical care and directions for future research.